2013
DOI: 10.1590/s1980-85852013000200007
|View full text |Cite
|
Sign up to set email alerts
|

Migração, retorno e circularidade: evidência da Europa e Estados Unidos

Abstract: O retorno faz parte do projeto migratório, contudo, enquanto uns retornam outros permanecem. A recente crise econômica é um dos fatores que intensificou o retorno. Este artigo ilustra as dinâmicas de retorno de emigrantes brasileiros nos Estados Unidos e em quatro países europeus -Portugal, Reino Unido, Holanda e Noruega, incluindo os processos de estranhamento, adaptação e circularidade ao longo do tempo. Os dados nos permitem considerar que as condições no destino constituem um elemento central nas estratégi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As we have seen in the previous section there have been many 'macro' economic and political developments in recent history which have contributed to return migration, but, as I will demonstrate, at the level of individual experience, the reasons for returning are much more diverse. Pereira and Siqueira (2013) acknowledge that while, 'the current economic condition in Brazil and Europe is undoubtedly an important factor driving the return' (9), they argue that this is only one determinant amongst many. They found that factors such as changing family or relationship circumstances and the emotional longing (the Portuguese concept of saudade) caused by being away from one's homeland often played a major role in influencing the decision to return.…”
Section: Returnmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have seen in the previous section there have been many 'macro' economic and political developments in recent history which have contributed to return migration, but, as I will demonstrate, at the level of individual experience, the reasons for returning are much more diverse. Pereira and Siqueira (2013) acknowledge that while, 'the current economic condition in Brazil and Europe is undoubtedly an important factor driving the return' (9), they argue that this is only one determinant amongst many. They found that factors such as changing family or relationship circumstances and the emotional longing (the Portuguese concept of saudade) caused by being away from one's homeland often played a major role in influencing the decision to return.…”
Section: Returnmentioning
confidence: 99%
“…They thus seek to establish the limits to traditional migration theories that privilege economic "pushpull" factors in explaining migration patterns. Similarly, in their study of return migration from the United States and Europe to Brazil, Pereira and Siqueira (2013) attribute only partial causality to economic factors, highlighting the effect of emotional and familial ones. They also draw attention to what they term "life-style migrants," who frame their migration decisions in terms of personal enrichment rather than economic motivation.…”
Section: The Literature On Brazilian Migrationmentioning
confidence: 99%